Analisis Pengendalian Kualitas Produk Teh Hitam dengan Pendekatan Lean-Six Sigma Method di PT. Teh XY - Endang Widuri Asih; Mega Rif'ah; La Ode Rain; Arie Pohandry (Journal of Industrial and Engineering System, 2021)
Teh XY is a black tea processing company engaged in the plantation sector, after further research it was found that some of the tea powder produced had production defects at least, there are about 15 kg that must be reworked because the water content produced does not meet the set standards (3-4%). This study aims to analyze the quality control of black tea products by identifying the relationship between types of waste at work stations and measuring the sigma level value. The method used to identify the relationship between waste that occurs is using the Waste Relationship Matrix and making a control chart graph based on production data and then calculating the DPMO value and Sigma Level to measure the company's production capability level. The results of this study indicate that the largest percentage level for waste that has the most influence on other types of waste is waste of motion (22.50%) in the sorting stage and the waste that is often affected is inventory (19.63%) at the milling stage. Based on the graph of the control chart, the data on the proportion of defects in the control chart shows that there is only a defect proportion value equal to the LCL value, namely in the 7th sample on January for quality I black tea production. sigma value of 2.31 with a DPMO value of 210605. This shows that for every one million opportunity there will be a possibility of 210605 units of rework products. Meanwhile, for quality III, it has a sigma value of 2.55 with a DPMO value of 150661.